2013
DOI: 10.1167/iovs.13-11910
|View full text |Cite
|
Sign up to set email alerts
|

Directing Adult Human Periodontal Ligament–Derived Stem Cells to Retinal Fate

Abstract: Primary human PDLSC could be directed to retinal progenitors with competence for photoreceptor differentiation. Human neural crest-derived PDL is readily accessible and can be an ample autologous source of undifferentiated cells for retinal cell regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 51 publications
5
63
0
1
Order By: Relevance
“…When the monolayer cells were placed in low attachment culture supplemented with CEE, they formed spheroids with an efficiency of 4.8%. This was similar to our earlier report showing ~4% efficiency 35. Spheroid formation appeared to be essential for PDL cells to differentiate towards CSK lineage.…”
Section: Discussionsupporting
confidence: 92%
“…When the monolayer cells were placed in low attachment culture supplemented with CEE, they formed spheroids with an efficiency of 4.8%. This was similar to our earlier report showing ~4% efficiency 35. Spheroid formation appeared to be essential for PDL cells to differentiate towards CSK lineage.…”
Section: Discussionsupporting
confidence: 92%
“…PDLSC have the potential to form neurosheres, three-dimensional floating cell clusters containing neural stem/progenitor cells [13]. Moreover, recent studies have demonstrated the generation of retial cells from PDLSC by the formation of neurospheres and inhibition of Wnt and BMP signalings [14]. Our recent study demonstrated that semaphorin 3A (Sema3A) plays a crucial role in preserving stem cell properties of PDLSCs; the expression level of Sema3A was stronger in multipotent human PDL cell lines compared with low-differentiation potential lines, and Sema3A-overexpressing low-differentiation potential PDL clones increased ESC-and MSCrelated marker expression and enhanced capacity to differentiate into osteoblasts and adipocytes [15].…”
Section: Characteristic Of Periodontal Ligament Stem Cellsmentioning
confidence: 99%
“…Notably, their differentiation capacity is not only limited to mesenchymal derivatives as they are able to generate ectodermal progeny [109][110][111][112]. Exposure of PDLSCs to E. coli or P. gingivalis LPS resulted in activation of NF-κB, production of IL-6 and IL-8, increased their proliferation rate and negatively influenced their osteogenic differentiation potential [17,113].…”
Section: Other Adult Stem and Progenitor Cellsmentioning
confidence: 99%